De Wachters van de Nacht en het eindtijddenken - Jansma, Lammert Gosse (Religie & Samenleving, 2017)
The Watchmen of the Night is a small religious group based in Aalten (in the Dutch province of Gelderland), that lives in the expectation of Jesus Christ’s imminent return to the earth. The Watchmen consider themselves belonging to the historicist school of interpretation of biblical prophecies. They expect the seventh vial of God’s wrath (Rev. 16:17) to be poured out soon and think the period 2017-2018 will be of crucial significance. In this article their prophecies concerning the end of times are presented and the question is discussed what will be the consequences for the group and its views when these predictions will be confronted with the (possible contradictory) reality of 2017-2018.